DOI: 10.26756/th.2022.538
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modelling and Optimization of Rotary Friction Welding Parameters of High-Density Polyethylene Pipes (HDPE). (c2022)

Abstract: Rotary friction welding (RFW) is a highly efficient and sustainable process for joining both metals and plastics. The welding process parameters of RFW must be carefully selected to ensure a good quality weld with minimum energy consumption. Few studies in the literature simulate RFW of plastics and none aim to optimize the welding process parameters. This study aims to optimize the process parameters of the continuous drive rotary friction welding of high-density polyethylene (HDPE) pipes. To simulate the RFW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…5. With a tool rotation speed of 1100 (rpm), side flash was reduced and with increased rotational speed set to 0.48 (radians/min) in all four welds, it was found that the behavior of the outer surface may depend on welding parameters as reported in previous studies [14][15][16][17][18]. Visual inspection was performed to detect potential voids or defects such as cracks, flashing, surface tunnels, wormholes, and lack of penetration.…”
Section: Fig 4 Schematic Drawing Of the Device Designed To Fix Parts ...mentioning
confidence: 73%
See 1 more Smart Citation
“…5. With a tool rotation speed of 1100 (rpm), side flash was reduced and with increased rotational speed set to 0.48 (radians/min) in all four welds, it was found that the behavior of the outer surface may depend on welding parameters as reported in previous studies [14][15][16][17][18]. Visual inspection was performed to detect potential voids or defects such as cracks, flashing, surface tunnels, wormholes, and lack of penetration.…”
Section: Fig 4 Schematic Drawing Of the Device Designed To Fix Parts ...mentioning
confidence: 73%
“…Low-density polyethylene (LDPE) has a lower degree of crystallinity than high-density polyethylene (HDPE). The latter is more crystalline, less branched, less flexible, and denser [14]. Many kinds of research [6][7][8][9][10][11] have been done on FSW for sheets of polymers in order to improve the welding condition.…”
Section: Introductionmentioning
confidence: 99%